Prevention and control of coronavirus disease 2019 (COVID-19) in public places. (1st January 2022) - Pan, Lijun; Wang, Jiao; Wang, Xianliang; Ji, John S.; Ye, Dan; Shen, Jin; Li, Li; Liu, Hang; Zhang, Liubo; Shi, Xiaoming; Wang, Lin
Abstract: Public places favor the transmission of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) due to dense population, large personal mobility, and higher contact opportunities. In order to protect the health of general public in operating public places during COVID-19 pandemic, this study proposed general precautions and control strategies from perspective of operation management, social distancing, cleaning and disinfection, and personal protection. In addition, with regard of risk level, specific precautions and control strategies were proposed for living service places, outdoor places, and confined places. The comprehensive application of above recommendations could effectively interrupt the spread of COVID-19, and protect the health of general public in public places. This study proposed general and specific precautions and control strategies in public places during COVID-19, and suggested further improvement of pandemic response.